The Impact of Village Fund Program in Developing Physical Infrastructure: Case on Construction Value Across Provinces in Indonesia - Mochamad Thoriq Akbar; Estro Dariatno Sihaloho (MediaTrend, 2019)
Indonesia is the largest archipelago country with over than 260 million population. Yet, its archipelagic state makes it hard for the Indonesian government to distribute its income equally, causing severe poverty in certain regions. To overcome this problem, the role of construction industry is very crucial. Many papers say construction industry plays an important role to achieve socio-economic development goals in providing shelter, physical infrastructure, employment, and higher economic growth. Knowing the importance of construction sector, especially in physical infrastructure, President of Indonesia, Joko Widodo, focuses on accelerating infrastructure development. To equally distribute the development between rural and urban areas and shorten the level of inequality, in 2015 Indonesian government made a program in a form of fiscal transfers called Village Fund program. The objective of this paper is to measure the impact of Village Fund program in developing physical infrastructure across provinces in Indonesia. This paper used panel data with Random Effect Model to analyze the marginal effect of Village Fund in construction sector. The finished construction value is used as the dependent variable. As the independent variable, this paper uses the amount of Village Fund given and Gross Domestic Regional Product (GRDP) as the control variable in 33 provinces that participated in Village Fund program during 2015 and 2016. Setting with α = 0.01, the result shows that Village Fund program has a marginal positive effect to finished construction value. Every one percentage point change in Village Fund increases the amount of construction value finished by 0.033%. For the other variable, every 1% increase in GRDP also increase the construction value by 0.41%. We hope this paper could be useful to evaluate the implementation of Village Fund and as a base for making similar policies in the future. Keywords: Village Fund, Construction Value, Infrastructure, GRDP, Random Effect Model